High amplitude bubble continuous positive airway pressure decreases lung injury in rats with ventilator-induced lung injury. Issue 10 (October 2019) - Wu, Chun-Shan; Chou, Hsiu-Chu; Huang, Liang-Ti; Lin, Chun-Mao; Lin, Yen-Kuang; Chen, Chung-Ming
Abstract : Background: Bubble continuous positive airway pressure (BCPAP) has been used in neonates with respiratory distress for decades; however, the optimal setting for BCPAP circuits remains unknown. This study compared the gas exchange efficiency and lung protection efficacy between conventional and high-amplitude BCPAP devices. Methods: We compared gas exchange, lung volume, and pulmonary inflammation severity among rats with ventilator-induced lung injury (VILI) that were treated with conventional BCPAP (BCPAP with an expiratory limb at 0°), high-amplitude BCPAP (BCPAP with an expiratory limb at 135°), or spontaneous breathing (SB). After mechanical ventilation for 90 minutes, the rats were randomly divided into four groups: a control group (euthanized immediately; n = 3), an SB group (n = 8), and two BCPAP groups that received BCPAP with the expiratory limb at either 0° (n = 8) or 135° (n = 7) for 90 minutes. Results: The high-amplitude BCPAP group exhibited significantly lower alveolar protein, lung volume, and Interleukin-6 (IL-6) levels than did the SB group. The high-amplitude BCPAP group exhibited significantly lower IL-6 levels than did the conventional BCPAP group. The two BCPAP groups demonstrated no difference in gas exchange efficiency. Conclusion: High-amplitude BCPAP reduced lung inflammation and alveolar overdistension in rats with VILI after mechanical ventilation was ceased. Thus high-amplitude BCPAP may offer a superior lung protective effect than conventional BCPAP.